La función social y psicológica del mito. - Martínez Herrera, Manuel (2012)
This article takes up the main theoretical concepts concerning the social explanation of myth. In relation to the psychological conception it contrasted junguian and freudian positions considering the place and role of the mythology within these theoretical constructs and their implications for phylogenetic and ontological level. Deep Hermeneutic is proposed as theory and social and psychological research method for the analysis and understanding of myths and legends because it promotes the integration of psychic and cultural reality in which are develop these human productions.